Kill it to save it : an autopsy of capitalism's triumph over democracy - Dolgon, Corey (Policy Press, 2017)
For decades, American voters have been convinced to support public policies that only benefit those in power. But how do the powerful extract consent from citizens whose own self-interest and collective well-being are constantly denied? And why do so many Americans seem to have given up on quality public education, on safe food and safe streets, on living wages - even on democracy itself? This book lays bare the hypocrisy of contemporary US political discourse, documenting the historical and theoretical trajectory of capitalism's triumph over democracy. Tackling the interconnected issues of globalization, neoliberalism, and declining public institutions, the author argues that American citizens now accept reform policies that destroy the public sector (seemingly in the public interest) and a political culture that embraces what Stephen Colbert calls "truthiness" - a willingness to agree to arguments that feel right "in the gut" regardless of fancy science or messy facts. In a narrative that stretches from the post-Vietnam War era to the present parade of political reality TV and debates over Black Lives Matter, the author dismantles US common-sense cultural discourse.